2020
DOI: 10.1038/s41598-020-59309-4
|View full text |Cite
|
Sign up to set email alerts
|

A Highly-sensitized Response of B-type Natriuretic Peptide to Cardiac Ischaemia Quantified by Intracoronary Pressure Measurements

Abstract: B-type natriuretic peptide (Bnp) secretion is stimulated by cardiac dysfunction. However, it is unclear how finely myocardial ischaemia contributes to BNP secretion and whether increases in BNP secretion contribute to coronary vasodilation. this study investigated the direct interaction between plasma Bnp levels and cardiac ischaemia using the baseline distal-to-aortic pressure ratio (pd/pa). We examined the baseline Pd/Pa and fractional flow reserve (FFR) in 167 patients with intermediate coronary stenosis. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In recent studies, many mechanisms, including myocardial ischemia, have been shown to contribute to BNP release, and BNP level has also been shown to be a useful clinical indicator in the diagnosis and prognosis of cardiovascular diseases. [10][11][12][13] Furthermore, it has been reported that BNP has vasodilator effects on the coronary artery system and that BNP primarily acts on both epicardial coronary arteries and coronary microvessels. [10,12] Due to its release in response to increased wall tension, it represents a higher degree of myocardial dysfunction in acute coronary syndrome patients with low left ventricular ejection rate and high BNP levels, with a high risk of congestive heart failure and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, many mechanisms, including myocardial ischemia, have been shown to contribute to BNP release, and BNP level has also been shown to be a useful clinical indicator in the diagnosis and prognosis of cardiovascular diseases. [10][11][12][13] Furthermore, it has been reported that BNP has vasodilator effects on the coronary artery system and that BNP primarily acts on both epicardial coronary arteries and coronary microvessels. [10,12] Due to its release in response to increased wall tension, it represents a higher degree of myocardial dysfunction in acute coronary syndrome patients with low left ventricular ejection rate and high BNP levels, with a high risk of congestive heart failure and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Furthermore, it has been reported that BNP has vasodilator effects on the coronary artery system and that BNP primarily acts on both epicardial coronary arteries and coronary microvessels. [10,12] Due to its release in response to increased wall tension, it represents a higher degree of myocardial dysfunction in acute coronary syndrome patients with low left ventricular ejection rate and high BNP levels, with a high risk of congestive heart failure and mortality. [14] BNP level was found to be higher, particularly in patients with three-vessel involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The path analysis was performed using the IBM SPSS AMOS software program (version 25, Amos Development Corporation, Meadville, PA, USA). We have previously described how to write a path model [5][6][7][8][9][10][11][12][13][14] . In brief, the current models show the relationship between clinical factors and the LV cavity sizes or LVEF using some hierarchical regression models.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In many areas, SEM plays an important role in understanding how the relationship among observed variables might be generated by an effect of interaction. Recently, we constructed several ideal models of a path diagram due to the solution of some disease status 5 14 . In this study, we tried to examine the effect of respective risk factors, such as aging, gender difference, body mass index (BMI), hypertension, diabetes, and dyslipidemia, on LV cavity sizes at the timing of systole and diastole in patients with IHD by using SEM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation